Calcium and vitamin D intake by postmenopausal women with osteoporosis in Spain: an observational calcium and vitamin D intake (CaVIT) study - Fan T; Nocea G; Modi A; Stokes L; Sen SS (Clinical Interventions in Aging, 2013)
Tao Fan,1 Gonzalo Nocea,2 Ankita Modi,3 Leah Stokes,1 Shuvayu S Sen1 1Global Outcomes Research, Merck & Company, Whitehouse Station, NJ, USA; 2Department of Outcomes Research, Merck, Sharp and Dohme Spain, Madrid, Spain; 3Global Human Health, Outcomes Research, Merck & Company, Whitehouse Station, NJ, USA Background: Osteoporotic fractures are important causes of morbidity, mortality, and increased health care costs. However, the risk of osteoporotic fractures can be decreased, with clinical studies supporting the use of calcium and vitamin D supplements to promote bone health. Vitamin D insufficiency is widespread, particularly among postmenopausal women with osteoporosis, and this indicates that dietary intake is suboptimal, even though vitamin D supplements are widely available. Methods: We conducted an observational study, using telephone surveys, to estimate vitamin D and calcium intake and the use of prescription osteoporosis medications in Spanish women aged ≥ 50 years with osteoporosis. Results: Among the study participants, mean dietary calcium intake was 1239 mg/day and generally appeared sufficient in terms of the recommended daily intake guidance documents. Participants aged ≥ 75 years had a significantly lower mean dietary calcium intake (988 mg/day), thus one-half were below the level advised by the World Health Organization. Daily calcium intake was also lower in participants who were not taking prescription medications for bone health. Dietary vitamin D intake was 167 IU/day, which is well below both the established target dose (400 IU/day) and the more recent, higher guideline recommended for postmenopausal women (800–1300 IU/day). Dietary vitamin D intake was even lower for participants aged ≥75 years (120 IU/day) and was not related to the use of bone health prescription medications. Conclusion: These results support the need for greater promotion of the benefits of higher vitamin D intake in Spanish women with osteoporosis. Keywords: osteoporotic fractures, prescription osteoporosis medications, dietary supplements, recommended dietary intake